PESAN DARI SLEBOR: ANALISIS WACANA KRITIS TERHADAP FENOMENA BAHASA TULIS STIKER SEPEDA MOTOR - Slamet Setiawan; Yustus Sentus Halum (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
One of the interesting phenomena in the use of written language is found in motor cycle stickers. The use of language is able to reveal social dimension and show social culture of a given society. This study focuses on messages in the motorcycle stickers: 1) describing patterns of language structures and other linguistic elements; 2) describing relationship patterns among participants; and 3) unsealing what and how socio-cultural phenomena. Theoretical Framework in this study refers to what is stated by Fairclough (1995): Critical Discourse Analysis (CDA). CDA is discourse analysis which involves socio-cultural phenomena expressed through the use of language. Based on 70 motor cycle stickers; using descriptive qualitative method; and applying Fairclough theory, it is found that: 1) Language patterns used in the stickers are casual type which employ short and incomplete structures. 2) There are three strong relationship patterns among participants: motorcycle rider, social class, and gender. 3) There are three main reflections drawn from social phenomena: social classes; Secondly, socio-politic policy applied for gender equality; phenomena of how bahasa gaul influences the use of proper and correct Bahasa Indonesia.